Análise dialélica entre genótipos comerciais de milho verde para características relacionadas à produtividade - Bertagna, Filipe Augusto Bengosi (2016)
Maize is one of the most exploited cereals of the world . Although much of the final destination of maize production in Brazil is for dry grains, different market niche markets are booming, such as green corn. With the objective to evaluate the general and specific combining abilities seven hybrid and two commercial varieties, the nine parents were crossed in a diallel scheme through its 72 combinations, 36 hybrids F1's and 36's reciprocal F1 hybrids. Togheter with his parents and two controls were evaluated in the alpha balanced lattice design in two locations in the city of Sabáudia/PR and Maringá/PR. Five agronomic traits were evaluated: female flowering, plant height, ear height, number of ears and yield of unhusked ears. The analysis of variance were applied on the experimental data. Through the adjusted means, Griffing (1956) diallel analysis methodology were applied on the experimental data, in order to measure the general and specific combining abilities. The commercial hybrid AM606 showed outstanding GCA for to female flowering, while hybrids AM606, AM811 and CD316 for plant height, AM811 and CD316 hybrids for ear heights, AM811, CD316 and CD393 for number of ears , and AM811 and CAT02 for yield of unhusked ears. Such hybrids can be recommended for a intrapopulation breeding programs. The hybrids AM811 x AG1051 and AG1051 x CAT02 showed desirable values of SCA for yield of unhusked ears, and are recommended for reciprocal recurrent selection programs. The AM811 genotype combained several desirable traits simultaneously, Therefore, interpopulational breeding methods are recommended.